2010
DOI: 10.1007/s10157-010-0334-8
|View full text |Cite
|
Sign up to set email alerts
|

Association between cystatin C and inflammation in patients with essential hypertension

Abstract: This study showed that cystatin C is a marker of inflammation as well as renal function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
62
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(66 citation statements)
references
References 31 publications
1
62
1
2
Order By: Relevance
“…A correlation between cystatin C and age is to be expected, as GFR declines with age [27]. The association between cystatin C and inflammatory markers has been described by some authors [25,28,29], although this may be expected as inflammation is activated in renal insufficiency. However, the only study adjusted for measured GFR still suggested a weak relationship between CRP and cystatin C [30,31].…”
Section: Discussionmentioning
confidence: 89%
“…A correlation between cystatin C and age is to be expected, as GFR declines with age [27]. The association between cystatin C and inflammatory markers has been described by some authors [25,28,29], although this may be expected as inflammation is activated in renal insufficiency. However, the only study adjusted for measured GFR still suggested a weak relationship between CRP and cystatin C [30,31].…”
Section: Discussionmentioning
confidence: 89%
“…27,[47][48][49] Further evaluations of the role of cystatin C and its correlation with and regulation by inflammatory cytokines will improve the utility of this protein as a marker of renal function. 50,51 Clearly, there remains the need to further evaluate the utility of cystatin C as a marker of renal function. For the current cohort, we determined the threshold of cystatin C > 1.0 mg/ liter had a positive predictive value of only 0.57 and 0.12 for eGFR < 90 and < 60 ml/min/1.73 m 2 , respectively, and a negative predictive value of 0.64 and 0.99 for eGFR < 90 and < 60 ml/min/1.73 m 2 , respectively (data not shown).…”
mentioning
confidence: 99%
“…In adult kidney transplant receipients, cystatin C levels have been reported to be increased in a dose-dependent fashion in steroid use (35). In addition, cystatin C levels are known to be affected by systemic inflammatory conditions atherosclerosis and hypertension, presence of thyroid dysfunction and tumor (36)(37)(38)(39). These interactions should be considered in clinical practice.…”
Section: Discussionmentioning
confidence: 99%